Trojan Grey Ware at Tel Miqne-Ekron - Allen, Susan Heuck (Bulletin of ASOR, 1994)
This article examines Grey Ware, a class of ceramics, characteristic of Troy Periods VI and VIIa, associated with Homer's Troy. Found in a well-stratified 13th century B. C. context at the inland site of Tel Miqne-Ekron, it demonstrates material evidence of contact between Troy and the Canaanite settlement shortly after the accepted date of the Trojan War.